PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Evi Kurniawati Anwar; Hunaepi Hunaepi; Ida Royani (Bioscientist : Jurnal Ilmiah Biologi, 2015)
The formulation the problem asked in this study is “is there any significant influence of cooperative TGT learning model towards students’ critical thinking ability?” Meanwhile, this research is aimed to know whether or not there is any significant influence of cooperative TGT learning model towards students’ critical thinking ability.  The type of the research in this study is experimental research in which the researcher uses nonequivalent control group design. The population of the study is the whole number of the VII grade students of SMPN SATAP 1 Wanasaba. The researcher takes the two classes as the sample of the study; those two classes are VIIA as the experimental group and the VIIB as the control group of the study. The result of data analysis in this study show the result that the result gained by the students before having the treatment is lower than students’ score after having the treatment. The result of t-calculation shows that the t-test is 0.678 and the value of t-table at the significance level 5% is 1.679. Based on the result of data analysis, it can be inferred that the t-test is higher than the value of t-table which means that the alternative hypothesis is accepted and the null hypothesis is rejected. Thus, the study concluded that there is any significant influence of cooperative TGT learning model towards students’ critical thinking ability.